Hybrid project management methodologies as a sign for organizational ambidexterity - S. A. Titov; N. V. Titova (Управленческие науки)
Project management plays an important role in the modern economy and public administration. Trends in project management have a significant impact on the performance of companies, public organizations, and programs for the socio-economic development in Russia. One of the interesting developments in project management is the expansion of hybrid methodologies, which combine tools and approaches of flexible and predictive approaches.This article aims to study the forms, results, and types of hybrid project management methodologies through the lens of the concept of organizational ambidexterity. Methodologically, the research is based on a systematic review of the Russian-language scientific literature on project management hybrid methodologies and organizational ambidexterity, as well as a qualitative content analysis of selected papers.The results of the study indicate that there are significant similarities between key aspects of hybrid methodologies and organizational ambidexterity. The authors conclude that hybrid project management methodologies can be considered as the instruments of organizational ambidexterity. As practical recommendations, the authors propose to expand the use of hybrid methodologies in the management of not only project-based firms, but also in other organizations, as well as in the management of socio-economic programs, especially in conditions of high uncertainty. The potential of hybrid methodologies to improve organizational ambidexterity and thereby simultaneously ensure the stability and flexibility organizations makes them invaluable tools to increase the resistance organizations and strategic programs to technological disruptions, socio-economic crises, and global shocks.